HOW ECONOMIC DYNAMICS INFLUENCE POVERTY: THE MODERATING POWER OF THE HUMAN DEVELOPMENT INDEX - Zahirah, Qonitah Rifda; Wibowo, Muhammad Ghafur; Musthofa, Muhammad Wakhid; Julina, Julina (Jurnal Al-Iqtishad, 2025)
This study explores how economic dynamics shape poverty levels in Indonesia, with a particular focus on the moderating influence of the Human Development Index (HDI). Utilizing a quantitative approach, data were gathered from 34 provinces across Indonesia over the period 2020–2024. Key variables examined include the open unemployment rate, Gross Regional Domestic Product (GRDP), population size, and regional minimum wage, while HDI functions as a moderating factor. The analysis employed multiple linear regression via the Generalized Least Square (GLS) method, followed by Moderated Regression Analysis (MRA) using EViews 12 software. By integrating panel data techniques and interaction effect assessments, the study reveals that both unemployment and population size significantly and negatively impact poverty reduction. In contrast, GRDP shows no statistically significant direct effect. The regional minimum wage demonstrates a significant influence, though its direction varies based on model specifications. Notably, HDI emerges as a powerful factor that not only significantly reduces poverty but also amplifies the negative impact of population size on poverty levels. However, its moderating role on other economic variables remains statistically insignificant. These insights underscore the intricate nature of poverty in Indonesia and emphasize the critical need for inclusive, human-centered development policies to drive meaningful and sustainable poverty alleviation.